Pentingnya pendidikan karakter bagi peserta didik jenjang Madrasah Ibtidaiyah - Asibly, Mohammad (Maliki Interdisciplinary Journal, 2024)
Character education is the initial foundation for creating students who have good morals or morals.Understanding character education is important, especially at the development level of Madrasah Ibtidaiyah (MI) children. Character education forms students to emulate good role models by understanding the figure of the Prophet Muhammad. Character education is an effort to instill various positive values ​​and habits in students, so that they can behave and act in accordance with religious norms, culture and national character. Instilling these character values ​​is very important to overcome various problems of deviant behavior and morals that often occur in our daily lives.